Potential Self-contamination: Improper Hygiene Procedure of Using Masks - Simatupang, Meithyra Melviana; Veronika, Erna; Sitepu, Olvariani (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
Using masks has become popular as an effort to prevent COVID-19. This increased the public consumption of masks. But in practice, this effort might cause other problems. The survey arranged to observe the potential contamination form from using masks. Specifically, it is a procedure when using and removing an inappropriate mask This descriptive study is a cross-sectional study. Data collection was carried out using a questionnaire filled in by 152 respondents aged ≥15-years-old who lived in the Jabodetabek area through a link shared online on various social media. Workingat the healthcare facility was the exclusion criteria for the participants. Fabric masks were the most commonly used. The majority replaced mask with the new or clean one once a day. Touched outer side of masks was the habit of most participants with lack of hand-hygiene practice. Potential self-contamination from inhaling pathogens, direct or indirect, released by the infected person when coughing, sneezing, even when talking, sourced themselves or others. Environmental contamination could occur due to lack of hand hygiene practice before wear masks, and after-touch while in use and after-remove it. Hence, educate the community for proper procedure use of masks and hand hygiene practice is necessary to prevent contamination and spread of diseases.